Minor Salivary Gland Neoplasms of Palate: Case Series with Differential Diagnosis and Review of Literature - Kamala Rawson; Basavaraj Kallali; Arun George; Admaja K Nair (Wolters Kluwer Medknow Publications, 2017)
Minor salivary gland tumors are infrequent, accounting for 10-15% of all salivary neoplasms. The most common intraoral site is palate, accounting for more than 50% of cases followed by lips, cheek mucosa, tongue, and floor of the mouth. Despite their relatively low frequency, minor salivary gland neoplasms represent a heterogeneous group of lesions, with a broad range of histological types and growth patterns imposing a diagnostic dilemma for the clinicians. Here we are reporting four cases of minor salivary gland neoplasms, all presented as palatal swellings of similar characteristics, and a review of literature is done for the same.